Valvontakapitalismi kuluttajan näkökulmasta - Lukkari, Tomi Petteri (2024)
Surveillance capitalism is a business based on making money from the digital traces left by people. The business behind surveillance capitalism is characterised by the fact that data collected by companies about their users is fed into a production process that turns the data into predictive products. These predictive products allow companies to predict future consumer behavior and use it to make a profit. Data is collected on all user activity on digital platforms. All user data is relevant, including users' Facebook likes, Google searches, emails, text messages, photos, songs listened to and videos watched. Online advertising also collects huge amounts of data through individual clicks whenever consumers use the internet or mobile apps. In the advertising network, the data that is circulated through cookies includes the consumer's device, what they have viewed and for how long. This thesis consists of a literature review and a qualitative study conducted through interviews. The study thus consists of a theoretical and an empirical part. The aim of the study was to investigate how aware consumers are of the practices of surveillance capitalism and its impact on their consumption behavior, and what the effects of surveillance capitalism are from the consumer's and society's perspective. The interviews revealed that consumers perceive the forms of surveillance capitalism in their daily lives, but their knowledge of its deeper logic is limited. The interviews also revealed that surveillance capitalism has an impact on consumers' consumption behavior and their conscious choices. From a consumer perspective, the main effects of surveillance capitalism relate to the privacy violations caused by the capture and resale of consumer data. From a society perspective, the main negative effects identified in the literature are the dominance of technology giants and disinformation.